Histology and ultrastructure of male reproductive system of the Indian Spiny lobster Panulirus homarus (Decapoda: Palinuridae) - Lakshmi Pillai, S. (2014)
The spiny lobster Panulirus homarus, distributed along the Southeast and Southwest coasts of India, is an important commercial species having mariculture potential. Despite its importance, the structural and ultrastructure features of male gonads from this species have received scarce attention. Hence this study was aimed to describe the male reproductive tract of the species, using standard histological and electron microscopy techniques. Gonads from 94 specimens of P. homarus ranging in carapace length 37mm-92mm from Vizhinjam (Southwest coast of India.) were obtained and processed for the study (Histology-70 numbers & ultrastructure-24 numbers). The male reproductive system consists of paired testis and vas deferens located in the cephalo-thoracic region. Macroscopically, the reproductive tract was observed in lobsters >35mm carapace length. In immature testis, spermatogonia were seen which measured 6.9-13.8µm in diameter and in the mature testis primary (5.4-5.9µm) and secondary spermatocytes (2.8-3µm) and spermatids (2.2-2.4µm) were present. Each vas deferens consists of proximal and distal portions. The spermatophoric mass begins formation in the proximal vas deferens. In the distal vas deferens the spermatophoric mass containing the spermatozoa are arranged in packets towards the periphery by the gelatinous matrix produced by the typhlosole. Ultrastructurally, the spermatogonia have lamina, nucleus and mitochondria like bodies, the primary spermatocytes have nucleus, dense chromatin and vacuolated cytoplasm and the spermatids have mitochondria, endoplasmic reticulum and centrioles. The endoplasmic reticulum and the nuclear envelope in the spermatids form the acrosome. The radial arms with microtubules are formed in association with the dense endoplasmic reticulum, near the nucleus. The sperm has a spherical structure with the nucleus, lamellar region, spikes and acrosome. This is the first comprehensive report of the structure of the male gametes and spermatogenesis in P. homarus from Indian waters.